EXPLORATION OF LANTUNG WOOD LEATHER WITH DESIGN THINKING METHOD FOR PRODUCT DEVELOPMENT OF LANTUNG BENGKULU MSMEs - Mochammad Charis Hidayahtullah; Eka Legya; Yuafni; Sugiyanto; Naimah Putri; Fauzi Ashari; Latifah Listyalina; Wahyu Ratnaningsih (Politek ATK Yogyakarta Press, 2022)
Indonesia is one of the countries that have contributed to the apparel, leather, and textile industry in the international market. Not only that, but Indonesian MSME handicrafts are also one of the commodities that can increase the country's foreign exchange, one of which is the lantung bark craft from Bengkulu. However, the creative industry is constantly facing competition with the entry of cheap products from China that get easy access with the increasing e-commerce technology. Providing value for the Lantung Bengkulu MSME products to compete locally and globally, one of the steps is to apply the Design Thinking Method and take the distinctive character of the stylized Serawai Tribe Weaving in the exploration process. The results of this study have obtained data that 47 Bengkulu women consumers as much as 89.4% like the results of the re-design and exploration of lantung shoes that have been designed. In determining the selling price of MSME Lantung Bengkulu should also set a price range of Rp. 110.000 to Rp. 500.000 because it corresponds to the purchasing power of female consumers in Bengkulu. The results of this study directly contribute to providing product value to the typical Bengkulu Lantung MSMEs. The Design Thinking method has been successfully increasing the value of the Lantung Bengkulu MSME products, this method can be applied to similar research to develop local MSMEs in Indonesia.